Complexes of BiCl3 with hydrazone derived ligands: a Möbius-like discrete metal chelate versus a salt-like porous polymeric structure. (27th May 2020) - Akbari Afkhami, Farhad; Mahmoudi, Ghodrat; Miroslaw, Barbara; Qu, Fengrui; Gupta, Arunava; Frontera, Antonio; Zubkov, Fedor I.; Zangrando, Ennio; Safin, Damir A.
Abstract : Reaction of BiCl3 with hydrazone derived ligands yielded a new Möbius-like discrete metal chelate [Bi(L I )Cl3 ] and a salt-like porous polymeric structure ([H2 L II ]2 [BiCl5 ]·EtOH) n . Abstract : In this work we have synthesized and characterized a new helical complex of BiCl3, namely [Bi(L I )Cl3 ], fabricated with an extremely bulky ligand, 1, 2-diphenyl-1, 2-bis((phenyl(pyridin-2-yl)methylene)hydrazono)ethane (L I ). The same reaction of BiCl3 with N ′-(4-hydroxybenzylidene)isonicotinohydrazide (HL II ) has allowed us to obtain a salt-like porous polymeric structure ([H2 L II ]2 [BiCl5 ]·EtOH) n . As evidenced from the single crystal X-ray analysis data, complex [Bi(L I )Cl3 ] is a Möbius-like discrete metal chelate, where the Bi III atom is seven-coordinated in a distorted pentagonal bipyramidal N4 Cl3 geometry and the organic ligand L I adopts a helical twist conformation. The structure of compound ([H2 L II ]2 [BiCl5 ]·EtOH) n comprises monoprotonated non-coordinated organic molecules [H2 L II ] + counterbalanced by a [BiCl5 ] 2− anionic fragment, which, in turn, forms a 1D zig-zag polymeric chain. The organic molecules are arranged in a centrosymmetric fashion yielding a hydrogen bonded tetramer with a rectangular cavity of dimensions 7.55 × 9.02 Å. The tetramers are stacked through weak intermolecular interactions, yielding 1D infinite channels. Thus, complex ([H2 L II ]2 [BiCl5 ]·EtOH) n was found to be a porous organic–inorganic hybrid compound. By using DFT calculations we have analyzed and rationalized the molecular electrostatic potential (MEP) surfaces and, through the quantum theory of the "atoms-in-molecules" (QTAIM) computational tool, the hydrogen bonding interactions observed in the solid state of both crystal structures, focusing on the competition between O–H⋯O and N–H⋯O hydrogen bonds in ([H2 L II ]2 [BiCl5 ]·EtOH) n .